2022
DOI: 10.1007/s12672-022-00580-4
|View full text |Cite
|
Sign up to set email alerts
|

LINC01089 blocks malignant progression of thyroid cancer by binding miR-27b-3p to enhance the FBLN5 protein level

Abstract: LINC01089 suppresses the malignant progression of breast, colorectal, and non-small cell lung cancers. However, the function of LINC01089 in thyroid cancer has not yet been elucidated. Here, The Cancer Genome Atlas (TCGA) database showed that LINC01089 expression is remarkably reduced in thyroid cancer tissues. Lower LINC01089 expression was correlated with higher tumor stage and regional lymph node metastasis. Furthermore, LINC01089 overexpression effectively blocked thyroid cancer cell proliferation, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…It is well-established that cancer-suppressive lncRNAs can interact with many cancer-promoting miRNAs and inhibit their functions [ 22 ]. Here, we performed subcellular fractionation to determine the cellular localization of PGM5-AS1.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-established that cancer-suppressive lncRNAs can interact with many cancer-promoting miRNAs and inhibit their functions [ 22 ]. Here, we performed subcellular fractionation to determine the cellular localization of PGM5-AS1.…”
Section: Resultsmentioning
confidence: 99%
“…Hsa-miR-27a-3p has been verified to be involved in the development of PTC [ 30 ]. LINC01089 can block the malignant progression of TC by binding hsa-miR-27b-3p to increase the level of FBLN5 protein [ 31 ]. TGFBR3 expression is down-regulated in PTC tissues and is associated with OS of patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on the study of Qian et al in 2021, in lung cancer cells, LNC01089 regulates the miR-301b-3p/STARD13 interaction axis, and through this mechanism, this lncRNA could decrease the migration rate of BC cells(Qian et al, 2021). LNC01089 also regulates the miR-27b-3p/FBLN5 axis in thyroid cancer patients, and this mechanism could suppress the malignant development(Pan et al, 2022)There has been no previous research on the diagnostic utility of LNC01089 across any cancer form, and for the rst time, we showed that this lncRNA has a signi cant diagnostic capability for distinguishing cancer samples from normal samples based on ROC analysis.…”
mentioning
confidence: 99%